Body composition and psychophysical well-being of women practicing yoga - Aneta OMELAN; Justyna WISNIEWSKA; Robert PODSTAWSKI (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction: This study characterized yoga as a form of free-time physical activity by analyzing and evaluating the body composition of women who regularly practice yoga, and by describing the effect of yoga on their psychophysical health. Material and Methods: The study involved 94 women: 56 yoga practitioners and 38 Zumba participants. The subjects were surveyed with a questionnaire to elicit information about their socioeconomic status. Body composition was determined by bioelectrical impedance analysis. Differences were assessed with two-tailed chi-square tests and Student's t-tests. Results: The vast majority of the participants (89%) felt a positive influence of yoga on their mental well-being; 86% noticed an improvement in physical health. More than half of the subjects adhered to a diet; those who practiced yoga chose vegetarian (29%) and vegan (13%) diets more often than those who did Zumba. Yoga participants had a higher BMI than Zumba participants (24.19 vs. 23.43), but they had a lower percentage of fat (28.84% vs. 29.89%) and higher fat free mass (47.08 kg vs. 44.13 kg). Conclusions: Yoga practice positively affects the psychophysical well-being of women. Despite their higher BMI, yoga practitioners had a slightly more favorable body composition, which may indicate that yoga positively affects individual body components and body shape.